Investigation of tensile strength properties for AlSi-based polyester powder coatings applied by plasma spray [Plazma püskürtme yöntemi̇yle uygulanmiş AlSi/poli̇ester esasli kaplamanin mukavemet ve mi̇kroyapi özelli̇kleri̇ni̇n i̇ncelenmesi̇] - (:unkn) unknown (My University, 1999)
Plasma spray coating are widely used for industrial purposes. Since plastic and plastic based composite powder materials are highly resistant to the atmospheric conditions, chemicals and impact loadings, there is an increasing interest towards them. In this study, failure types and the effect of failure types on the tensile strength were investigated for AlSi based polyester powder coatings applied by plasma spray. Coatings were applied with and without NiAl interlayers. In this way the effect of NiAl on the failure strength and failure types were investigated and the results were presented. Tensile tests were carried out according to the ASTM C 633-79 standard.
Keywords: Failure type; Powder coating; Tensile strength